TheRevolutionaryDiscourseinFreneauand Zakaria’s Selected Poems - Mr. AhmedDEBDOUCHE, Ms.Zina MILOUDI (My University, 2019)
ABSTRACT Thepresentthesisjuxtaposestwopoets,PhilipFreneaufromtheUSAandMoufdiZakaria fromAlgeria,whosepoemsillustratewhatis widelyknownasliteratureoftherevolution.In thisresearch,theoverallpurposeistopinpointandunmasktheliteraryfunctionofthe variousideologiesembodiedwithintheselectedpoems,andtodeterminethereasonbehind choosingthemasmajorstructuringelements.Toachievethesegoals,thestudyresortstothe CriticalDiscourseAnalysisapproachwhichaimsatexploringcriticallyideological standpointsastheyareexpressedandmanifestedindiscourse.Thisstudyis significantinthe sensethatitattemptsinarelativelygroundbreakingwayto drawclosertwoliteratures- AlgerianandAmerican-whichseemdifferent,but happentohaveseveralthingsincommon. Afterinvestigation,ithasbeenrevealedthatnature,politics,andreligionareeffectivelyused asideologicalmeansforliberatingthealienated,oppressedindividualsfromtheircolonial rulers,andthatwords arenolessimportantthanweaponsinthestruggleforindependence.
Keywords: Keyterms:Literature,revolution,ideologies,criticaldiscourse,independence